Eye Tracking of Attentional Allocation During Processing of Game Technologies: Association with Daily Playtime and Gaming Consequences - Gilbertson, Rebecca J.; Leff, Dustyn J.; Downs, Edward (Addicta: The Turkish Journal on Addictions, 2022)
This study used eye tracking as a measure of attention to examine how preference for video gaming images may change across a continuum of video gamers (casual to heavy). During the eye tracking procedure, participants (ages 18–26, N = 73; 43 men, 30 women) viewed 45 image pairs, presented in random order, composed of video gaming, alcohol, and neutral images. Following, participants completed questionnaires about video gaming and alcohol behavior. Findings showed that self-reported measures of experience, including video gaming quantity (i.e., daily playtime) and consequences, showed a significant positive relationship to eye tracking metrics of initial fixation and dwell time toward video game images. Results also showed that participants who reported loss of control (i.e., binge gaming) also demonstrated greater preference for video game images. The findings suggest that the attentional allocation during the processing of video game images in young adults may be enhanced by experience such as daily playtime. Changes in attentional allocation and cue reactivity may further contribute to the development of problematic video gaming behavior through prioritization of video gaming over other appetitive behaviors. These findings have basic science and clinical implications, including treatment for gaming disorder.